Power sector asset stranding effects of climate policies - Saygin, D; Rigter, J; Caldecott, B; Wagner, N; Gielen, D (Taylor and Francis, 2019)
Energy sector decarbonization to limit the temperature rise to well-below 2°C will result in stranded assets and capital stock replacement before its technical lifetime ends. In this paper, stranded assets in the global power sector are quantified based on a simplified bottom-up analysis that considers the capital stock turnover of fossil fuel-fired power plants in the G20 countries between 2015 and 2050. Power sector transformation starting now based on accelerated deployment of renewables results in US dollar (USD) 927 billion of global power sector stranded assets by 2050. Stranded coal assets would represent around three-quarters of total stranded assets value and China alone would represent 45% of the total. Delaying action to mitigate climate change until 2030 doubles stranded asset value. Countries should consider assets’ age profile characteristics in their decision making. Early action and avoidance of investments in new carbon-intensive assets can minimize stranded asset risks.